O efeito das mulheres nos conselhos e diretorias na sustentabilidade empresarial - Rigon, Letícia (2023)
The presence of women in the top management of companies represents an important factor for the development of Corporate Governance, which contributes to the optimization of results achieved through control, monitoring, organization and strategies aimed at assertive decisions. Female management is marked by characteristics such as: transparency, monitoring, patience, sincerity and concern for long-term issues, which tend to leverage corporate sustainability results. Using descriptive statistics, correlation and multiple linear regression analysis, this study sought to analyze the effect of women on boards and directors on corporate sustainability (financial, market, environmental and social) in countries with (France, Finland, Italy and the United Kingdom) and without mandatory regulation (Germany, Brazil, Spain, Ireland and Switzerland) of women in such positions. The results showed the existence of a positive and significant relationship between women on the Board of Directors and Executive Board in financial and market performance both in companies with some type of regulation on the presence of women in senior management, and in companies from countries without this type of regulation. In addition, corroborating the previous literature, the positive impact of women on the environmental and social disclosure of the analyzed companies was noticed. Such evidence contributes to the literature related to the themes of women in senior management and Corporate Sustainability, by reaffirming previous findings and explaining the divergent results. Therefore, the results found reinforce the argument that women play an important role in the corporate governance of companies and contribute to increasing corporate sustainability (financial, market, environmental and social). For the corporate environment, the results bring important highlights to the female characteristics that tend to leverage the results of companies when in a leadership position. Thus, the main practical implication for companies that seek to develop corporate sustainability is that the increase of women on the board of directors and executive management leads to better financial and market results and greater disclosures of environmental and social sustainability. Finally, it is emphasized that the findings of this research can help policy makers to develop policies aimed at appointing women in senior management, given the benefits for corporate sustainability, more pronounced in countries that have some regulation of women in positions of company management.